Pentingnya Pendidikan Moral Sejak Anak Sekolah Dasar - Heru Siswanto (rogram Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2018)
People said that education is development. It creates choices and opportunities for people, reduces the twin burdens of poverty and diseases, and gives a stronger voice in society. For nations it creates a dynamic workforce and well-informed citizens able to compete and cooperate globally - opening doors to economic and social prosperity. However, the main purpose of education is not only to create skillful and bright brain individual, but also a moral citizen. Moral education is becoming an increasingly popular topic in education. Media reports of increased violent juvenile crime, sexual harassment, corruption, illegal logging, and other violence-one of them taken place at one of the